Feasibility and acceptability of home delivery of water for dental caries control in Latinx children—“Sediento por una Sonrisa,” Thirsty for a Smile: Single-arm feasibility study - Cunha-Cruz, Joana; Ko, Linda K.; Mancl, Lloyd; Rothen, Marilynn L.; Harter, Catherine; Hilgert, Juliana B.; Koday, Mark K.; Davis, Stephen (Frontiers in Public Health, 2022)
Background: Outcomes of surgical treatments under general anesthesia for early childhood caries of young children are poor requiring retreatment within two years. Dietary sugar is an ideal intervention target given that it is the most prominent risk factor for dental caries and the increasing evidence of successful interventions to reduce its intake. Our aim is to investigate the feasibility and acceptability of the Thirsty for a Smile intervention, designed to promote consumption of water in lieu of sugar sweetened beverages, among children who underwent surgery for early childhood caries and their caregivers, mostly from Latino heritage. Methods: A single-arm feasibility study was conducted in a dental practice from a community health center in eastern Washington State. Bottled water was delivered to the participants’ homes and caregivers received patient-centered counseling for setting goals to increase children’s water intake and reduce sugar sweetened beverages consumption. We assessed feasibility and acceptability of the intervention and study procedures through participation rates, interviews and a questionnaire completed by the caregivers. Data was analyzed and themes and descriptive statistics presented. Results: Twenty-two dyads of caregivers and their children between 3 and 8 years old who recently had surgical treatment for early childhood dental caries were enrolled. Study assessments were completed by more than 90% of participants, except for the final 24-hr dietary recall (73%). Dietary counseling, both in person and brief telephone calls, was highly acceptable to the caregivers, and they also reported their children enjoyed and used the water bottles. On a scale from 1 to 10, the average rating for the helpfulness of the dietary counseling component for changing child’s drinking habits was 9.62 and for the water delivery component, 8.86. Conclusions: This study tested the feasibility of conducting a trial in a dental practice setting, and the acceptability among caregivers of young children who underwent surgery for early childhood caries. It demonstrated that the Thirsty for a Smile intervention and study processes were feasible and acceptable. The study provides useful information for implementation of a two-arm randomized controlled trial in this setting, and may also benefit other researchers attempting to test similar interventions.